Assessment of disease activity using a whole-body MRI derived radiological activity index in chronic nonbacterial osteomyelitis - Martina Capponi; Denise Pires Marafon; Flaminia Rivosecchi; Yongdong Zhao; Manuela Pardeo; Virginia Messia; Laura Tanturri de Horatio; Paolo Tomà; Fabrizio De Benedetti; Antonella Insalaco (BMC, 2021)
Abstract Background Based on the recently developed ChRonic nonbacterial Osteomyelitis MRI Scoring tool (CROMRIS), we developed a radiological activity index (RAI-CROMRIS) to obtain a quantification of the overall bone involvement in individual patients. Methods Whole Body Magnetic Resonance Imaging (WB-MRI) images were scored according to parameters included in the RAI-CROMRIS: bone marrow hyperintensity, signal extension, soft tissue/periosteal hyperintensity, bony expansion, vertebral collapse. These parameters were evaluated for each bone unit yielding a score from 0 to 7 and summed up as RAI-CROMRIS including all bone units. We assessed clinical disease activity using a physician global assessment (PGA) and radiological findings in 76 treatment-naïve patients; 46 of 76 were evaluated at 6 and 12 months after initial WB-MRI. Quantitative variables were compared using the Mann-Whitney U test for unmatched groups and the Wilcoxon signed-rank test for paired groups. Correlation was evaluated using Spearman's rank coefficient (rs). Results There was a significant correlation between RAI-CROMRIS and PGA (r s = 0.32; p = 0.0055), between RAI-CROMRIS and presence of elevated erythrocyte sedimentation rate (p = 0.013) and C-reactive protein (p = 0.0001) at baseline. The RAI-CROMRIS decreased from a median of 17 at baseline to 12 at 6 months (p = 0.004) and remained stable (median 11) at 12 months. A correlation between the RAI-CROMRIS and the PGA was observed at baseline (r s = 0.41; p = 0.004) and during follow up at 6 months (r s = 0.33; p = 0.025) and 12 months (r s = 0.38; p = 0.010). The baseline RAI-CROMRIS (median 20) was significantly higher in patients who subsequently received bisphosphonates than in patients who received other treatments (median 12) and decreased significantly after bisphosphonates (p = 0.008). Conclusions The RAI-CROMRIS was correlated with clinical and laboratory measures of disease activity showing significant short-term changes following treatment with bisphosphonates. This tool could be used in clinical practice and clinical trials after validation.